MANAGEMENT, BUDGETING AND COST-BENEFIT ANALYSIS: OPERATIONAL AND STRATEGIC ASPECT - Pavel P. Kholodov; Galina I. Zyablitskaya (Статистика и экономика)
The article describes the problems of management of costs, results and assets of an organization in conditions of economic instability. The analysis of new and innovative systems for obtaining information about the costs, the use of new types of cost accounting is given. Management decision making mechanism is pointed out based on this analysis.